Comparative wood anatomy of root and stem in Styrax camporum (Styracaceae) - Machado, Sílvia R. [UNESP]; Angyalossy-Alfonso, Veronica; De Morretes, Berta L. (Brill Academic Publishers, 1997)
Styrax camporum Pohl is a shrub common in the cerrado vegetation of south-eastern Brazil. Root and stem wood in Styrax camporum differ quantitatively and qualitatively. Quantitative differences follow normal expectations: roots have wider and longer vessel elements, a lower vessel frequency, a lower ray frequency, and wider rays. Qualitative features of the roots are: simple perforation plates, vestured pits, and septate libriform fibres; qualitative features of the stems are: multiple perforation plates, non-vestured pits, and non-septate fibre-tracheids. Based on generally accepted evolutionary trends, root wood of Styrax camporum has more specialized features than stem wood. Additional comparative studies of stem and root anatomy are needed to determine if such differences between root and stem anatomy are widespread, and consistent with the lines of specialization observed in monocotyledons.
Keywords: root; stem; Styracaceae; Styrax camporum; wood anatomy